Xylem resistance to embolism: presenting a simple diagnostic test for the open vessel artefact. Issue 1 (3rd May 2017) - Torres‐Ruiz, José M.; Cochard, Hervé; Choat, Brendan; Jansen, Steven; López, Rosana; Tomášková, Ivana; Padilla‐Díaz, Carmen M.; Badel, Eric; Burlett, Regis; King, Andrew; Lenoir, Nicolas; Martin‐StPaul, Nicolas K.; et al.
Summary: Xylem vulnerability to embolism represents an essential trait for the evaluation of the impact of hydraulics in plant function and ecology. The standard centrifuge technique is widely used for the construction of vulnerability curves, although its accuracy when applied to species with long vessels remains under debate. We developed a simple diagnostic test to determine whether the open‐vessel artefact influences centrifuge estimates of embolism resistance. Xylem samples from three species with differing vessel lengths were exposed to less negative xylem pressures via centrifugation than the minimum pressure the sample had previously experienced. Additional calibration was obtained from non‐invasive measurement of embolism on intact olive plants by X‐ray microtomography. Results showed artefactual decreases in hydraulic conductance ( k ) for samples with open vessels when exposed to a less negative xylem pressure than the minimum pressure they had previously experienced. X‐Ray microtomography indicated that most of the embolism formation in olive occurs at xylem pressures below −4.0 MPa, reaching 50% loss of hydraulic conductivity at −5.3 MPa. The artefactual reductions in k induced by centrifugation underestimate embolism resistance data of species with long vessels. A simple test is suggested to avoid this open vessel artefact and to ensure the reliability of this technique in future studies.